1998
DOI: 10.1002/(sici)1520-6394(1998)8:1+<96::aid-da15>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Depression and eating disorders

Abstract: Both depressive disorders and eating disorders are multidimensional and heterogeneous disorders. This paper examines the nature of their relationship by reviewing clinical descriptive, family‐genetic, treatment, and biological studies that relate to the issue. The studies confirm the prominence of depressive symptoms and depressive disorders in eating disorders. Other psychiatric syndromes which occur with less frequency, such as anxiety disorders and obsessive‐compulsive disorders in anorexia nervosa, or pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(46 citation statements)
references
References 82 publications
(108 reference statements)
2
42
0
2
Order By: Relevance
“…Moreover, patients with ED were reported to suffer from a wide spectrum of depressive symptoms [42]. Specific characteristics of MD and such a common depressive symptomatology even not meeting MD full criteria highlight the importance of considering also these psychopathological aspects in assessment, monitoring, and treatment of these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients with ED were reported to suffer from a wide spectrum of depressive symptoms [42]. Specific characteristics of MD and such a common depressive symptomatology even not meeting MD full criteria highlight the importance of considering also these psychopathological aspects in assessment, monitoring, and treatment of these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A significant improvement in mood was observed after pramipexole, despite that no patient was considered clinically depressed at any point in the study. Mental depression is associated with loss of food intake and weight loss,13 and antidepressant treatment (anticholinergic, serotoninergic, and noradrenergic drugs) causes a variable extent of weight gain 14. During clinical trials, it has been shown that pramipexole has mood‐stabilizing or ‐elevating effects 15.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated depression levels in women with disordered eating patterns have been reported elsewhere (Casper, 1998). On the other hand, clinical depression is typically manifested by loss of appetite, though atypical depression is characterized by vegetative symptoms that include increased appetite and weight (Davidson, Miller, Turnbull, & Sullivan, 1982).…”
Section: Concerns About Post-cessation Weight Gainmentioning
confidence: 83%